The Happy Prince - "Wild, Oscar" (MM Publications: London, 2001)
tale of compassion and sacrifice. The golden statue of a once-joyful prince sees the suffering of the poor in his city. With the help of a kind swallow, he gives away his gold and jewels to help those in need. The swallow, devoted to the prince, stays behind and dies from the cold. In the end, both are discarded by the city but find eternal reward in heaven.
Keywords: Fiction